Atomic-scale metal modified carbon nitride and polar BiOIO3 heterojunction catalyst as well as preparation method and application thereof
By modifying carbon nitride and polar BiOIO3 heterojunction catalysts by atomic metals, combining piezoelectric and optical characteristics, the problem of low production efficiency of photocatalytic H2O2 is solved, and efficient and low-cost H2O2 synthesis is achieved.
Patent Information
- Application Number
- CN202411998036.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
AI Technical Summary
In the existing photocatalytic technology, the low production efficiency, poor selectivity and slow kinetics of H2O2 are limited by its application in industrial environments.
The catalyst is prepared by atomic metal modification of carbon nitride and polar BiOIO3 heterojunction catalyst by one-step calcination and hydrothermal treatment, combining piezoelectric and optical characteristics to improve the utilization rate of natural light energy.
It significantly improves the selectivity and synthesis efficiency of H2O2, reduces the energy barrier of redox, and achieves low-cost and efficient H2O2 synthesis.
Smart Images

Figure CN119680613A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic technology, and in particular to an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst, and a preparation method and application thereof. Background Art
[0002] Hydrogen peroxide (H2O2) is a versatile and environmentally friendly oxidant that is widely used in wastewater purification, disinfection, textiles, organic synthesis and other fields. However, the traditional high-temperature anthraquinone production method has major challenges, including high energy consumption, the use of expensive palladium catalysts, technical complexity and the production of excessive byproducts. An attractive alternative is the photosynthesis of H2O2, which uses water and oxygen as inputs and sunlight as an energy source. This method is energy-saving, mild reaction conditions, and environmentally friendly, which meets the growing requirements of sustainable development. However, the efficiency and overall effect of photocatalytic H2O2 production are often limited by low selectivity and sluggish oxygen reduction reaction (ORR) kinetics, which hinder its application in industrial settings. These challenges arise from the following factors: (1) a limited number of active sites; (2) insufficient charge separation transfer and too fast charge recombination; (3) low mass transfer efficiency; and (4) the formation of unwanted intermediates or byproducts (Angewandte Chemie International Edition 2024, e202421356). Therefore, developing low-cost and efficient catalysts to jointly achieve the goal of efficient H2O2 synthesis is highly desirable but also challenging.
[0003] Exploring robust and selective active sites is crucial for enhancing H2O2 production via these pathways. Single atom catalysts (SACs) have isolated active sites and 100% atomic utilization on supports to create efficient active / adsorption sites. In recent years, constructing internal or interfacial electric fields has become a rising star in promoting various catalytic processes, with the advantages of facilitating charge transfer / separation and optimizing redox potentials. Internal electric fields are usually formed by the polarization of inhomogeneous charge distribution between different constituent layers and are widely present in piezoelectric materials, polar surface terminals, and heterostructured materials. Summary of the invention
[0004] The purpose of the present invention is to overcome the low selectivity and low efficiency defects of the above-mentioned prior art and to provide an atomic-level metal-modified carbon nitride and polar BiOIO3 (polar iodate) heterojunction catalyst, its preparation method and application. The catalyst is a heterojunction catalyst formed by a composite of atomic-level metal-modified carbon nitride and polar BiOIO3, which couples piezoelectric properties and optical properties, and can effectively improve the utilization rate of natural light energy, thereby improving the catalytic efficiency.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the present inventions provides an atomic-level metal-modified carbon nitride and polar iodate (BiOIO3) heterojunction catalyst, wherein the catalyst is composed of atomic-level metal-modified carbon nitride and composited with polar BiOIO3.
[0007] Furthermore, the catalyst is a heterojunction catalyst formed by a composite of atomic-level metal-modified carbon nitride and polar BiOIO3.
[0008] Furthermore, the metal has 10 Electronic configuration, such as antimony or gallium or indium or germanium; the polar BiOIO3 is a two-dimensional sheet structure with abundant surface oxygen vacancies.
[0009] Furthermore, the metal in the atomic-level metal is selected from one or more of antimony, gallium, indium and germanium.
[0010] Furthermore, the mass ratio of the atomic-level metal-modified carbon nitride to the polar BiOIO3 is (1:4) to (1:1).
[0011] The second aspect of the present invention provides a method for preparing a heterojunction catalyst of atomic-level metal-modified carbon nitride and polar iodate (BiOIO3), that is, a method for preparing a heterojunction formed by combining atomic-level metal-modified carbon nitride and polar BiOIO3, wherein the preparation method obtains the atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst by one-step calcination and hydrothermal treatment. The preparation method comprises the following steps:
[0012] S1, preparing atomic-level metal-modified carbon nitride by one-step calcination;
[0013] S2, preparing polar BiOIO3 by hydrothermal treatment;
[0014] S3, the atomic-level metal-modified carbon nitride powder obtained in step S1 and the polar BiOIO3 powder obtained in step S2 are dispersed in deionized water and ultrasonically treated to form solution E and solution F, and solution F is added dropwise to solution E, and after being ultrasonically mixed for 8 hours, it is transferred to a 100 ml polytetrafluoroethylene-lined stainless steel autoclave, placed in an oven, and heated at 140°C for 10 hours. The powder is collected by centrifugation and dried at 80°C for 12 hours to obtain a metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst.
[0015] Furthermore, the preparation method comprises the following steps:
[0016] S11: dissolving melamine in anhydrous ethanol and stirring until it becomes clear to form a solution A; dissolving melamine cyanurate in anhydrous ethanol and stirring to form a solution B; dispersing a metal precursor in anhydrous ethanol to form a solution C;
[0017] S12: Pour solution C into solution B and stir once, then mix with solution A, and stir twice at room temperature to obtain solution D;
[0018] S13: centrifuging the solution D obtained in step S12, collecting the sample, drying and grinding, and obtaining a powder to be calcined;
[0019] S14: calcining the powder to be calcined obtained in step S13 under an inert atmosphere to obtain atomic-level metal-modified carbon nitride.
[0020] S15: Polar BiOIO3 was prepared by a one-pot hydrothermal method. Bi(NO3)3·5H2O was dissolved in dilute nitric acid and then KIO3 was added. The mixture was stirred at room temperature for 2-3 hours. The suspension was then transferred to a 100 ml polytetrafluoroethylene-lined stainless steel autoclave, placed in an oven, and heated at 180°C for 16-18 hours. The powder was collected by centrifugation, washed alternately with ethanol and deionized water for 3 times, and dried at 80°C for 12 hours to obtain a dried powder.
[0021] S16: The dried powder obtained in step S15 is stirred in a KI solution at room temperature for 15-18 hours. The obtained sample is repeatedly washed with deionized water and dried at 80° C. for 12 hours to obtain polar BiOIO3 with abundant oxygen vacancies.
[0022] S17: The atomic-level metal-modified carbon nitride powder obtained in step S14 and the polar BiOIO3 powder obtained in step S16 are dispersed in deionized water and ultrasonically treated to form solution E and solution F, respectively. Solution F is added dropwise to solution E, and after being ultrasonically mixed for 8 hours, it is transferred to a 100 ml polytetrafluoroethylene-lined stainless steel autoclave, placed in an oven, and heated at 140°C for 10 hours. The powder is collected by centrifugation and dried at 80°C for 12 hours to obtain a metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst.
[0023] Furthermore, in the method for preparing an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst, the metal precursor is sodium hexafluoroantimonate (NaSbF6) or gallium chloride or germanium iodide or indium chloride or more thereof.
[0024] Furthermore, in the method for preparing an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst, the metal precursor is sodium hexafluoroantimonate (NaSbF6) or gallium chloride or germanium iodide or indium chloride, and the atomic-level metal is antimony or gallium or germanium or indium.
[0025] Furthermore, the molar ratio of melamine, melamine cyanurate and metal precursor is (10-12): (9-10): (10-25).
[0026] Preferably, the molar ratio of melamine, melamine cyanurate and metal precursor is (10-12):(9-10):20.
[0027] Furthermore, the molar ratio of melamine, melamine cyanurate and metal precursor is 10:10:20.
[0028] Furthermore, in step S12, the rotation speed of the first stirring is 500-600 rpm, and the stirring time is 60 min; the rotation speed of the second stirring is 500-600 rpm, and the stirring time is 1-2 h.
[0029] Furthermore, the inert atmosphere in step S14 is high-purity N2; in step S14, the calcination is specifically: heating from room temperature to 500-600°C at a heating rate of 5-8°C / min, maintaining at 500-600°C for 4-6h, and then naturally cooling to room temperature.
[0030] Furthermore, in step S15, the molar ratio of Bi(NO3)3·5H2O to KIO3 is (3-6):(1-3), and the concentration of the dilute nitric acid is 3-5 mol / L.
[0031] Preferably, the molar ratio of Bi(NO3)3·5H2O to KIO3 is 3:1, and the concentration of dilute nitric acid is 5 mol / L.
[0032] Furthermore, in step S16, the concentration of the KI solution is 0.01-0.4 mol / L.
[0033] Preferably, the concentration of KI solution is 0.2 mol / L.
[0034] Furthermore, in step S16, the stirring speed is 500-600 rpm, and the stirring time is 16 hours.
[0035] The third aspect of the present invention provides an application of the atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst, wherein the catalyst is used to efficiently catalyze the synthesis of H2O2 using H2O and O2 under sunlight and vibration conditions.
[0036] The catalyst can efficiently catalyze H2O and O2 to synthesize H2O2 under sunlight and vibration conditions.
[0037] Furthermore, the specific steps of the catalyst efficiently catalyzing H2O and O2 to synthesize H2O2 under sunlight and vibration conditions are:
[0038] S21: firstly, dispersing the catalyst into deionized water, and bubbling O2 into the deionized water for 1 h to reach saturation;
[0039] S22: A 300W xenon lamp (AM1.5G) was used to simulate the sunlight source and ultrasonic vibration frequency of 35-45kHz and power of 200-400W to catalyze the synthesis of H2O2. The catalytic reaction was carried out in an ultrasonic cleaning machine reaction system with a circulating water bath at a temperature of 20-25°C, and high-purity O2 was continuously blown in during the reaction.
[0040] Furthermore, the input ratio of the deionized water to the atomic-level metal-modified carbon nitride and the polar BiOIO3 heterojunction catalyst is 30 mL: (10-20) mg.
[0041] Preferably, the input ratio of the deionized water to the atomic-level metal-modified carbon nitride to the polar BiOIO3 heterojunction catalyst is 30 mL: 10 mg.
[0042] Compared with the prior art, the present invention has the following advantages:
[0043] 1. The present invention prepares an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst, which is a two-dimensional / two-dimensional (2D / 2D) heterojunction structure, and combines the advantages of single-atom catalysts to couple piezoelectric properties with optical properties, which can effectively improve the utilization rate of natural light energy, thereby improving catalytic efficiency. In particular, polar BiOIO3 forms a strong polarization field under vibration, regulates carriers at the 2D / 2D heterojunction interface and inhibits their recombination, producing more active oxygen. In addition, the high-intensity polarization field can also reduce the energy barrier of redox, thereby improving the overall efficiency of synthesizing H2O2.
[0044] 2. The atomic-level metal in the atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst of the present invention has d 10 The electronic configuration of metals (such as antimony or gallium or indium or germanium) enhances the adsorption of O2 and can eliminate the formation of the middle band of the band structure and promote the formation of *OOH, leading to an efficient two-electron oxygen reduction reaction.
[0045] 3. The atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst of the present invention has low cost and can be produced on a large scale, improves the selectivity and synthesis efficiency of H2O2, and also provides a general platform for regulating the reaction rate and path of the target redox reaction through conventional means. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1The X-ray diffraction patterns (XRD) of Example 1, Example 2, Example 3 and Comparative Example 4 of the present invention are shown in FIG. Figure 1 a is the X-ray diffraction pattern of Example 2 and Comparative Example 4; Figure 1 b is the X-ray diffraction pattern of Example 1 and Example 3.
[0047] Figure 2 The transmission electron microscope (TEM) images of Example 1 and Example 3 of the present invention are shown in FIG. Figure 2 a is a transmission electron microscope image (TEM) of Example 1 (20Sb-C3N4); Figure 2 b is a transmission electron microscopy (TEM) image of Example 3 (Sb-CN / 2BIO-I3); Figure 3 c is a high-resolution transmission electron microscopy image of Example 3 (Sb-CN / 2BIO-I3).
[0048] Figure 3 is a performance diagram of synthetic H2O2 in an embodiment of the present invention; wherein Figure 3 a is a comparison chart of the performance of synthesizing H2O2 under the conditions of light irradiation, ultrasound and simultaneous light irradiation and ultrasound in Example 1, Comparative Example 2 and Comparative Example 3 of the present invention; Figure 3 b is a performance diagram of catalytic synthesis of H2O2 under ultrasound in Example 2, Comparative Example 4, Comparative Example 5, Comparative Example 6 and Comparative Example 7 of the present invention; Figure 3 c is a performance diagram of synthesizing H2O2 under the conditions of simultaneous light irradiation and ultrasound of Comparative Example 8, Example 3 and Comparative Example 9 of the present invention. Figure 3 d is a performance diagram of synthesizing H2O2 under the conditions of light irradiation, ultrasound and simultaneous light irradiation and ultrasound in Example 1, Example 2, Example 3, Comparative Example 2, Comparative Example 10 and Comparative Example 11 of the present invention.
[0049] Figure 4 It is a schematic diagram of the application principle of the present invention. DETAILED DESCRIPTION
[0050] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0051] The present invention relates to an atomic-level metal-modified carbon nitride and polar iodate (BiOIO3) heterojunction catalyst, a preparation method and application thereof, wherein the catalyst is composed of a metal embedded in carbon nitride and then forming a heterojunction with polar BiOIO3; the metal has d 10The electronic configuration is atomically dispersed antimony. The prepared catalyst can synthesize H2O2 from H2O and O2. Compared with the prior art, the present invention prepares a two-dimensional / two-dimensional (2D / 2D) heterojunction structure, and combines the advantages of single-atom catalysts to couple piezoelectric properties and optical properties, which can effectively improve the utilization rate of natural light energy, thereby improving catalytic efficiency. 10 The electronic configuration of antimony (Sb) enhances the adsorption of O2 and promotes the formation of *OOH, resulting in an efficient two-electron oxygen reduction reaction. In particular, polar BiOIO3 forms a strong polarization field under vibration, regulates carriers at the 2D / 2D heterojunction interface and inhibits their recombination, polarizes H2O molecules to produce more active oxygen, and the high-intensity polarization field can also reduce the energy barrier of redox, thereby improving the overall efficiency of synthesizing H2O2. The present invention not only improves the efficiency of H2O2 synthesis, but also provides a general platform for regulating the reaction rate and path of the target redox reaction through conventional means.
[0052] Unless otherwise specified, various raw materials of the present invention can be purchased from the market or prepared according to conventional methods in the art.
[0053] Example 1
[0054] This embodiment provides an atomic-level metal-modified carbon nitride and a preparation method thereof.
[0055] The atomic-level metal-modified carbon nitride in this embodiment is an atomic antimony-modified carbon nitride catalyst, and the specific preparation method is as follows:
[0056] S1: Dissolve 10 mmol melamine in 30 mL anhydrous ethanol, stir at 600 rpm until clear, and form solution A at 70°C; dissolve 10 mmol cyanuric acid melamine in 30 mL anhydrous ethanol, stir at 600 rpm for 60 min to form solution B; disperse 20 mmol NaSbF6 in 20 mL anhydrous ethanol to form solution C;
[0057] S2: Pour solution C into solution B, stir at 600 rpm for 60 min, mix with solution A, and stir at 600 rpm for 2 h at room temperature to obtain solution D;
[0058] S3: centrifuging the solution D obtained in step S12 at a speed of 10000 rpm, collecting the sample, and drying and grinding at 80° C. to obtain a powder to be calcined;
[0059] S4: The powder to be calcined obtained in step S13 is heated at 5°C min under N2 atmosphere. -1 The sample was heated at 600 °C for 4 h at a heating rate to obtain an atomic antimony modified carbon nitride catalyst, which was recorded as 20Sb-C3N4.
[0060] Example 2
[0061] This embodiment provides a polar BiOIO3 with abundant oxygen vacancies and a preparation method thereof.
[0062] The specific steps are:
[0063] S1: Dissolve 3mmol Bi(NO3)3·5H2O in 40ml 5mol / L dilute nitric acid, the concentration of which is 5mol / L, and stir at room temperature until dissolved. Then add 1mmol KIO3 and stir at room temperature for 2h. Then transfer the suspension to a 100ml polytetrafluoroethylene-lined stainless steel autoclave, put it in an oven, and heat it at 180℃ for 16h. Collect the powder by centrifugation, wash it alternately with ethanol and deionized water for 3 times, and dry it at 80℃ for 12h to obtain the dried powder.
[0064] S2: The dried powder obtained in step S1 was stirred in 30 mL of 0.2 M KI solution at room temperature for 16 h. The obtained sample was repeatedly washed with distilled water and dried at 80° C. for 12 h to obtain polar BiOIO3 with abundant oxygen vacancies, which was recorded as BIO-I3.
[0065] Example 3
[0066] This embodiment provides an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst and a preparation method thereof.
[0067] The specific steps are:
[0068] 100 mg of 20Sb-C3N4 powder was dispersed in 20 mL of deionized water and ultrasonically treated to form solution E. 200 mg of BIO-I3 powder was dispersed in 20 mL of deionized water and ultrasonically treated to form solution F. Solution F was added dropwise to solution E. After ultrasonic mixing for 8 hours, the mixture was transferred to a 100 ml polytetrafluoroethylene-lined stainless steel autoclave, placed in an oven, and heated at 140°C for 10 hours. The obtained powder was collected by centrifugation and dried at 80°C for 12 hours to obtain an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst, recorded as Sb-CN / 2BIO-I3.
[0069] Example 4
[0070] like Figure 4As shown, this embodiment provides an application of atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst, and uses H2O and O2 to efficiently catalyze and synthesize H2O2 under sunlight and vibration conditions. First, Sb-CN / 2BIO-I3 is dispersed in deionized water, and high-purity O2 is continuously blown in for 1h until saturation. A 300W xenon lamp (AM 1.5G) is used to simulate the sunlight source and catalytically synthesize H2O2 under the action of ultrasonic vibration frequency of 40kHz and power of 200W. The catalytic reaction is carried out in an ultrasonic cleaning machine reaction system by controlling the temperature at 20-25°C through a circulating water bath, and O2 is continuously introduced during the reaction. The input ratio of deionized water to atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst is 30mL: 10mg.
[0071] Comparative Example 1
[0072] This comparative example provides a carbon nitride catalyst and a preparation method thereof.
[0073] The specific preparation method is:
[0074] S1: Dissolve 10 mmol of melamine in 30 mL of anhydrous ethanol, stir at 600 rpm until clear, and form solution A at 70°C; dissolve 10 mmol of melamine cyanurate in 30 mL of anhydrous ethanol, stir at 600 rpm for 30 min, and form solution B;
[0075] S: 2: Pour solution B into solution A, stir at 600 rpm for 60 min, and stir at 600 rpm for 2 h at room temperature;
[0076] S3: centrifuging the solution obtained in step S2 at a speed of 10000 rpm, collecting the sample, and drying and grinding at 80° C. to obtain a powder to be calcined;
[0077] S4: The powder to be calcined obtained in step S3 is heated at 5°C min-1 under N2 atmosphere. 1 The sample was heated at 600 °C for 4 h at a heating rate to obtain the C3N4 catalyst.
[0078] Comparative Example 2
[0079] This comparative example provides an atomic-level metal-modified carbon nitride catalyst and a preparation method thereof.
[0080] Compared with Example 1, the only difference is that 15 mmol NaSbF6 is added in step S1 to prepare an atomic antimony modified carbon nitride catalyst, which is recorded as 15Sb-C3N4.
[0081] Comparative Example 3
[0082] This comparative example provides an atomic-level metal-modified carbon nitride catalyst and a preparation method thereof.
[0083] Compared with Example 1, the only difference is that 25 mmol NaSbF6 is added in step S1 to prepare an atomic antimony modified carbon nitride catalyst, which is recorded as 25Sb-C3N4.
[0084] Comparative Example 4
[0085] This comparative example provides a method for preparing polar BiOIO3.
[0086] The specific steps are:
[0087] Dissolve 3mmol Bi(NO3)3·5H2O in 40ml 5mol / L dilute nitric acid, stir at room temperature until dissolved, then add 1mmol KIO3 and stir at room temperature for 2h. Then transfer the suspension to a 100ml polytetrafluoroethylene-lined stainless steel autoclave, put it in an oven, and heat it at 180℃ for 16h. Collect the powder by centrifugation, wash it alternately with ethanol and deionized water 3 times, and dry it at 80℃ for 12h, which is recorded as BIO.
[0088] Comparative Example 5
[0089] Compared with Example 2, the only difference is that 0.08 M KI solution is added in step S2, which is denoted as BIO-I1.
[0090] Comparative Example 6
[0091] Compared with Example 2, the only difference is that 0.1 M KI solution is added in step S2, which is recorded as BIO-I2.
[0092] Comparative Example 7
[0093] Compared with Example 2, the only difference is that 0.4 M KI solution is added in step S2, which is recorded as BIO-I4.
[0094] Comparative Example 8
[0095] Compared with Example 3, the only difference is 100 mg of 20Sb-C3N4 and 100 mg of BIO-I3, which is recorded as Sb-CN / BIO-I3.
[0096] Comparative Example 9
[0097] Compared with Example 3, the only difference is 100 mg of 20Sb-C3N4 and 400 mg of BIO-I3, recorded as Sb-CN / 4BIO-I3.
[0098] Comparative Example 10
[0099] This embodiment provides a carbon nitride and polar BiOIO3 heterojunction catalyst and a preparation method thereof.
[0100] 100 mg of C3N4 powder was dispersed in 20 mL of deionized water and ultrasonically treated to form solution E. 200 mg of BIO-I3 powder was dispersed in 20 mL of deionized water and ultrasonically treated to form solution F. Solution F was added dropwise to solution E. After being ultrasonically mixed for 8 hours, it was transferred to a 100 ml polytetrafluoroethylene-lined stainless steel autoclave, placed in an oven, and heated at 140°C for 10 hours. The powder was collected by centrifugation and dried at 80°C for 12 hours to obtain a heterojunction catalyst of carbon nitride and polar BiOiO3, which was recorded as CN / 2BIO.
[0101] Comparative Example 11
[0102] Compared with Example 4, the only difference is that the performance of synthesizing H2O2 is tested without adding a catalyst.
[0103] Performance Analysis:
[0104] Figure 1 The X-ray diffraction patterns (XRD) of Example 1 (20Sb-C3N4), Example 2 (BIO-I3), Example 3 (Sb-CN / 2BIO-I3) and Comparative Example 4 (BIO) show that no peak of metal Sb is found, indicating that Sb exists in the form of extremely small clusters or atoms. After treatment with KI, the characteristic peaks of BIO do not change, indicating that its structure has not changed. The characteristic peaks of the corresponding substances are detected in the composite heterojunction catalyst, indicating that a heterojunction has been successfully formed.
[0105] Figure 2 The transmission electron microscopy (TEM) images of Example 1 (20Sb-C3N4) and Example 3 (Sb-CN / 2BIO-I3) and the high-resolution transmission electron microscopy image of Sb-CN / 2BIO-I3 show that the morphology of 20Sb-C3N4 is two-dimensional flake-like. From the TEM image of Sb-CN / 2BIO-I3, it can be seen that the two-dimensional BIO-I3 nanosheets are wrapped by the two-dimensional 20Sb-C3N4. Although long-term ultrasonic dispersion is performed in the TEM measurement, there is still a close interface interaction between 20Sb-C3N4 and BIO-I3, as shown in FIG. Figure 2 c, which demonstrates the strong bonding between 20Sb-C3N4 and BIO-I3.
[0106] Figure 3a is a comparison chart of the performance of synthesizing H2O2 under the conditions of light, ultrasound and simultaneous light and ultrasound of Example 1 (20Sb-C3N4), Comparative Example 2 (15Sb-C3N4) and Comparative Example 3 (25Sb-C3N4). It can be seen from the figure that the performance of synthesizing H2O2 of C3N4 modified with metal Sb is obvious under light, while the performance of H2O2 synthesis under ultrasound is very low, and there is no obvious increase in the coupling between light and ultrasound, indicating that Sb-C3N4 is mainly sensitive to light. Figure 3 b is the performance diagram of Example 2 (BIO-I3), Comparative Example 4 (BIO), Comparative Example 5 (BIO-I1), Comparative Example 6 (BIO-I2) and Comparative Example 7 (BIO-I4) in catalytic synthesis of H2O2 under ultrasound. After BIO reacts with KI of different concentrations, its performance is improved under the action of ultrasound, indicating that the increase of vacancies on the surface of BIO helps to improve its polarity. However, when KI is 0.4M, its performance is reduced, indicating that its structure may be destroyed. Figure 3 c is the performance diagram of synthesizing H2O2 of comparative example 8 (Sb-CN / BIO-I3), embodiment 3 (Sb-CN / 2BIO-I3) and comparative example 9 (Sb-CN / 4BIO-I3) of the present invention under the conditions of simultaneous light irradiation and ultrasound. With the increase of BIO-I3 content, the performance of synthesizing H2O2 increases first and then decreases, which may be due to the decrease of 20Sb-CN content and the decrease of photogenerated carrier concentration. It shows that Sb-CN / 2BIO-I3 has the best ratio structure. Figure 3 d is the performance diagram of synthesizing H2O2 under the conditions of light, ultrasound and simultaneous light and ultrasound of Example 1 (20Sb-C3N4), Example 2 BIO-I3, Example 3 (Sb-CN / 2BIO-I3), Comparative Example 1 (C3N4), Comparative Example 10 (CN / 2BIO) and Comparative Example 11 (blank). In the absence of a catalyst, almost no H2O2 is produced. Compared with C3N4, 20Sb-C3N4 and CN / 2BIO, the performance of Sb-CN / 2BIO-I3 heterojunction catalyst in synthesizing H2O2 under simultaneous light and ultrasound is greatly improved, indicating that the composite catalyst (atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst) accelerates the transfer of carriers and inhibits their recombination under ultrasound. The polarization field strength generated by BIO-I3 under ultrasound reduces the reaction energy barrier, thereby improving the synthesis efficiency of H2O2.
[0107] The above-mentioned embodiments and comparative examples fully demonstrate the innovation of the present invention: the present invention provides an innovative atomic-level metal-modified carbon nitride and polar iodate (BiOIO3) heterojunction catalyst, which can synthesize H2O2 with low energy consumption and high efficiency. By constructing a two-dimensional / two-dimensional (2D / 2D) heterojunction structure and combining the excellent properties of single-atom catalysts, the present invention achieves efficient coupling of piezoelectric properties and optical properties, significantly improving the utilization rate of natural light energy and catalytic efficiency. In particular, the strong polarization field formed by polar BiOIO3 under vibration effectively regulates the carriers and inhibits their recombination, while promoting the polarization of H2O molecules to produce more active oxygen, reducing the redox energy barrier, and thus comprehensively improving the synthesis efficiency of H2O2. In addition, with d 10 The atomic-level metal antimony with electronic configuration significantly enhances the adsorption of O2 and promotes efficient two-electron oxygen reduction reaction. The catalyst of the present invention is not only low-cost and can be produced on a large scale, but also improves the selectivity and synthesis efficiency of H2O2, and provides a universal platform for regulating the reaction rate and path of the target redox reaction, which has important scientific value and practical significance.
[0108] It should be emphasized that the above-mentioned implementation mode is only a preferred scheme of the present invention. Those skilled in the art can make non-substantial improvements and substitutions based on the present invention, and these improvements and substitutions should also be regarded as falling within the scope of protection required by the present invention.
Claims
1. An atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst, characterized in that: The catalyst is a heterojunction catalyst formed by combining atomic-level metal-modified carbon nitride and polar BiOIO3; The metal in the atomic-level metal-modified carbon nitride has a 10 Electronic configuration; The polar BiOIO3 is a two-dimensional sheet structure and has surface oxygen vacancies.
2. The atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst according to claim 1, characterized in that: The metal in the atomic-level metal-modified carbon nitride is selected from one or more of antimony, gallium, indium, and germanium; The mass ratio of the atomic-level metal-modified carbon nitride to the polar BiOIO3 is (1:4) to (1:1).
3. A method for preparing an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst as described in any one of claims 1 to 2, characterized in that: The steps include: S11: dissolving melamine in anhydrous ethanol and stirring until it becomes clear to form a solution A; dissolving melamine cyanurate in anhydrous ethanol and stirring to form a solution B; dispersing a metal precursor in anhydrous ethanol to form a solution C; S12: Pour solution C into solution B and stir once, then mix with solution A, and stir twice at room temperature to obtain solution D; S13: washing and centrifuging the solution D obtained in step S12, collecting the sample, drying and grinding, and obtaining a powder to be calcined; S14: calcining the powder to be calcined obtained in step S13 under an inert atmosphere to obtain atomic-level metal-modified carbon nitride; S15: A polar iodate is prepared by a one-pot hydrothermal method. Bi(NO3)3·5H2O is dissolved in dilute nitric acid and KIO3 is added. The mixture is stirred at room temperature. The suspension is then heated. The powder is collected by centrifugation, washed, and dried to obtain a dried powder. S16: Stir the dried powder obtained in step S15 in a KI solution at room temperature, wash the obtained sample, and then dry it to obtain polar BiOIO3; S17: The atomic-level metal-modified carbon nitride obtained in step S14 and the polar BiOIO3 obtained in step S16 are dispersed in deionized water and ultrasonically treated to form solution E and solution F, respectively. Solution F is added dropwise to solution E, ultrasonically mixed and then heated. The powder is collected by centrifugation and dried to obtain an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst.
4. The method for preparing an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst according to claim 3, characterized in that: The metal precursor is sodium hexafluoroantimonate, gallium chloride, germanium iodide or indium chloride.
5. The method for preparing an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst according to claim 3, characterized in that: The molar ratio of melamine, melamine cyanurate and metal precursor is (10% 12): (9% 10): (10-25).
6. The method for preparing an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst according to claim 3, characterized in that: The molar ratio of Bi(NO3)3·5H2O and KIO3 is (3-6):(1-3), and the concentration of dilute nitric acid is 3-5 mol / L.
7. The method for preparing an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst according to claim 3, characterized in that: The inert atmosphere in step S14 is N2; In step S14, the calcination is specifically as follows: heating from room temperature to 500-600°C at a heating rate of 5-8°C / min, maintaining at 500-600°C for 4-6h, and then naturally cooling to room temperature.
8. An application of an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst as claimed in any one of claims 1 to 2, characterized in that: The catalyst is used for catalytically synthesizing H2O2 by utilizing H2O and O2 under sunlight and vibration conditions.
9. The use of an atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst for catalytic synthesis of H2O2 according to claim 8. , characterized in that: The specific steps of using the atomic-level metal-modified carbon nitride and polar BiOIO3 heterojunction catalyst to catalyze the synthesis of H2O2 using H2O and O2 under sunlight and vibration conditions are as follows: S21: dispersing the catalyst into deionized water, and bubbling O2 into the deionized water for 1-2 hours to reach saturation; S22: A 300W xenon lamp is used to simulate the sunlight source and ultrasonic vibration frequency of 35-45kHz and power of 200-400W is used to catalyze the synthesis of H2O2. The temperature of the catalytic reaction is controlled at 20-25℃, and high-purity O2 is continuously blown into the reaction process.
10. The use of an atomic-level metal-modified carbon nitride and a polar BiOIO3 heterojunction catalyst for catalytic synthesis of H2O2 according to claim 9, characterized in that: In step S17, the input ratio of the deionized water to the atomic-level metal-modified carbon nitride and the polar BiOIO3 heterojunction catalyst is 30 mL: (10-20) mg.
Citation Information
Patent Citations
Preparation method for carbon nitride supported monodisperse oxidation state metal atom catalytic material
CN106861746A
BiOIO3 / g-C3N4 heterojunction photocatalyst, preparation method and applications thereof
CN110694667A
I-doped BiOIO3 photocatalyst as well as preparation method and application thereof
CN116212900A
Atomic-scale metal embedded graphite carbon nitride catalyst as well as preparation method and application thereof
CN118416926A
Cited By
Piezoelectric functional material, piezoelectric functional material preparation method and water pollution treatment method
CN122343098A